ANALISIS KEMAMPUAN BERPIKIR KRITIS SISWA SMA DALAM MEMECAHKAN SOAL TENTANG STATISTIKA DATA BERKELOMPOK DENGAN MENGGUNAKAN TIPE KEPRIBADIAN (THINKING-FEELING) - Yuliana Br Aritonang; Lili Rohanita Hasibuan; Eva Julyanti (Universitas Bhinneka PGRI, 2025)
Education is a planned effort, in the learning process and creating a learning atmosphere so that students can develop their potential to become competent in the abilities they are learning. This research aims to analyze the critical Thinking skills of high school students in solving group data statistical problems and to see the differences between students with Thinking and Feeling personality types. With a qualitative descriptive design, the research results showed an average critical Thinking ability of 18.31 and a Thinking-Feeling personality type of 21.22. However, the t-Test shows that the difference is not statistically significant (t-count -6.19 t-table 1.66 at α 0.05), indicating that personality type does not have a significant effect on critical Thinking skills, so other factors such as teaching methods or learning experiences are more likely to play a role.